Land use in the dry subtropics: Vegetation composition and production across contrasting human contexts - Baldi, Germán (2012)
Dry subtropical regions, originally hosting xerophytic vegetation, are currently characterized by diverse land cover/use patterns. Using existing biophysical and socio-economic databases, we explored how human contexts influenced land cover, vegetation composition and agricultural production in five distant regions. On average, cultivated areas represented a minor proportion (<16%) of all the regions, except in Asia (74%). This proportion was positively associated with population density when considering all regions together (slope = 0.2 ha∗inh−1), but the association became weaker in low-population regions. While protected areas displayed highly similar life-forms across regions, non-protected natural vegetation areas presented large contrasts, suggesting different imprints of land management. The observed contrasts were more marked for cultivated vegetation, with different species and species diversities being found in each region. These contrasts likely reflect orientation toward national/global markets in the Australian and American regions and toward local markets/subsistence in Asian and African regions. Africa and Asia were characterized by low and similar per capita levels of food production (∼50 kg grain∗y−1∗inh−1 and ∼0.14 livestock units∗inh−1), in contrast to South America and Australia (585 kg grain∗y−1∗inh−1 and 10.2 units∗inh−1, respectively). This comparative perspective assisted in exploring the reciprocal influences between social-economic development and ecosystems that lead to alternative strategies of land management.